Potential Role of Cannabidiol on Sports Recovery: A Narrative Review - Rojas-Valverde, Daniel (Frontiers in Physiology, 2021)
The use of cannabidiol (CBD) among athletes is becoming extensive and frequent. This could be due to its elimination of CBD from the list of prohibited substances by federations and international institutions of sport. Also, CBD legalization, and production and commercialization allowance could rise it intake. This situation, despite the fact that the use and commercialization of cannabinoids has not ceased, has fueled the race to study their properties, benefits and risks for health and performance in athletes. Although there is evidence that suggests some beneficial properties such as anxiolytics, antidepressants, anti-inflammatory, antioxidants among others, the evidence presented so far is neither clear nor conclusive. In fact, there is a great gap in knowledge regarding the physiological pathways that explain the role of CBD in sports performance. This mini-review aims to expose the evidence suggesting that CBD has the potential to be used as part of strategies to recover from fatigue and muscle damage related to physical and cognitive exertion in sport.